Pharmaceutical Standardization of a Herbomineral Formulation (Jeeva Rasa Churna) for Vajeekarana - Kumar, Vikas (Asian Journal of Pharmaceutics (AJP), 2019)
Background: Vajeekarana deals with fertility, potency, and healthy offspring along with diseases like erectile dysfunction (ED). This is a widespread disease among men having negative impact on the quality of life of the patients and their partners. Aim: This study aims to prepare and characterize the formulation (Jeeva Rasa Churna [JRC]) used in ED. Materials and Methods: JRC has been prepared by homogeneous mixing of two mineral drugs, namely Shuddha Hingula and Shuddha Shilajatu and fine powder of five herbal ingredients, namely Akarakarabha, Ashwagandha, Shweta Mushali, Shatavari, and Vidarikanda. JRC was subjected to various physiochemical parameters such as moisture content, water-soluble extractive, thin-layer chromatography, and energy-dispersive X-ray spectroscopy (EDX) for its standardization. Results: The total of 3.750 kg of JRC was prepared using 150 g, Hingula and 3.600 kg of homogeneous mixture of Shuddha Shilajatu, Akarakarabha, Ashwagandha, Shweta Mushali, Shatavari, and Vidarikanda. It was observed that 5.6% moisture content and 1.80% water-soluble extractive were in JRC, respectively, and EDX study showed that formulation was free from heavy metals except mercury which is an ingredient of JRC. Conclusion: The physiochemical parameters of formulation JRC fall within the range of Ayurvedic pharmacopeia for Churna so it may be a safe and effective medicine for ED.